Secret windows essays and fiction on the craft of writing - King, Stephen frey50 (New York, NY Book-of-the Month Club, 2000)
This is an exlcusive Book-of-the-Month Club anthology of hard-to-find non-fiction pieces, little-known interviews, short stories, and articles about writing for those looking for direction on how to find their own "windows"--Or for anyone wishing to be touched by Stephen King's humor and wisdom.
Dave's Rag : "Jumper," "Rush call" -- "The horror market writer and the ten bears : a true story" -- Foreword to Night shift -- "On becoming a brand name" -- "Horror fiction" from Danse macabre -- "An evening at the Billerica [Massachusetts] Library" -- "The ballad of the flexible bullet" -- "How it happened" -- "Banned books and other concerns : The Virginia Beach lecture" -- "Turning the thumbscrews on the reader" -- "'Ever et raw meat?' and other weird questions" -- A new introduction to John Fowles's The collector -- "What Stephen King does for love" -- "Two past midnight : a note on 'Secret window, secret garden'" -- Introduction to Jack Ketchum's The girl next door -- "Great hookers I have known" -- "A night at the Royal Festival Hall" : Muriel Gray interviews Stephen King -- "An evening with Stephen King" -- "In the deathroom."
Keywords: King, Stephen -- 1947-; Authors -- 20th century -- American; Horror tales -- Authorship -- American